Approach to the Assessment and Management of Adult Patients With Atopic Dermatitis: A Consensus Document. Section III: Evaluation of Atopic Dermatitis Patients for Comorbidities. Issue 1 (November 2018) - Hong, Chih-ho; Sussman, Gordon; Turchin, Irina; Wiseman, Marni; Gooderham, Melinda J.
Atopic dermatitis (AD) is often associated with other atopic diseases, including asthma, allergic rhinitis, atopy-associated eye disorders, and eosinophilic esophagitis. Depression and anxiety are also comorbidities to AD that significantly affect quality of life and should be screened for in patients with AD. Links to other comorbidities such as cardiovascular disease and malignancy are considered inconclusive, but patient counselling and screening may be appropriate in some patients. This article highlights practical recommendations for the recognition and management of atopic and nonatopic comorbidities commonly associated with AD.